Pengaruh Penggunaan #skincareviral di Video TikTok Terhadap Minat Beli Skincare bagi Pengguna TikTok di Denpasar - Utami, Putu Hardayani; Ras Amanda, Ni Made; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
ABSTRACT The study explains the effect of using #skincareviral on the interest on buying facial serum skincare products on social media that is TikTok. TikTok is a social media that provides a place for its users to express themselves through video content. In today’s digital era, the use of hashtags as a way of marketing communication. Interactive marketing on TikTok has its own potential to become a viral trend. This research is quantitative. The research data collected through a survey method by distributing an online questionnaire as an instrument to 110 respondents with predetermined criteria. The results showed that the variable #skincareviral use on TikTok videos has a strong correlation and positive. This study proves that there is an effect of using #skincareviral in TikTok videos on the interest in buying facial serum skincare products of 89,9%, while the remaining 10,1% is influenced by other factors not mentioned in this research. Kata Kunci: Use of hashtag, Interest of Buys, TikTok.